Religious Practices in the Daily Performance of Kalipare Community - Kholil, Ahmad; Tamimullah, Tamimullah (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2023)
For every person, religion is the main principle, because it becomes the basis in thought and all its attitudes. This article is the result of research that discusses the religious understanding of Kalipare community and its practice in the behavior of their daily lives. This research was conducted in the southern region of Malang Regency based on Social Construction Theory initiated by Peter L. Berger and Thomas Luckman. The theory states that social reality is a double reality, subjective and objective, which proceeds through three dialectical moments namely; externalization, objectification and internalization. Thus, it can be understood that social reality is the result of the social construction created by man himself. In the context of this study, the social reality studied is the local wisdom of Selametan Desa (village thanksgiving) with its various processes, either sacred or not. The results show that; Kalipare's citizens believe that religion is the basis of all their attitudes and actions. Religion relates to faith which influences aspects of thought and action. The practice of religious community is shown in the daily behavior as a reflection of their religious understanding. The Kalipare community structure is made up of diverse cultures with a harmonious atmosphere of life. It is a local wisdom and it looks even clearer when they are conducting a ceremony called Selametan Desa (village thanksgiving) as a ceremony for the village "birthday". Community leaders become references in their everyday attitudes, especially those related to religion. This is supported by the authority of religious institutions represented in the apostasy of mosques and other religious institutions.